PENGARUH KEMASAN TERHADAP KEPUTUSAN KONSUMEN DALAM PEMBELIAN PRODUK INDUSTRI KECIL MAKANAN RINGAN PADA SUPERMARKET DI KOTA JAMBI - Sigit Indrawijaya (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2012)
Research aimed to know the effect of packaging, pricing and quality of consumer decisions in the purchase of Small Industrial Snack Foods products at supermarkets in the city of Jambi, research has been done in the Jambi city starting July 2010 until May 2011. This study is descriptive survey verifikatif using descriptive and explanatory methods. Packaging in the evaluation through the elements as well as visual, verbal elements and the protective function of the product. Data obtained through a questionnaire using a sample of consumer Small Industrial Snack Foods products at supermarket in the city of Jambi. Data were analyzed descriptively with cross tabulation and verifikatif analysis. The results showed that the factor packaging has the potential to encourage consumers to purchase Small Industrial Snack Foods Products at supermarket in the city of Jambi. Packaging affect consumer decisions in the purchase of Small Snack products in supermarkets in the city of Jambi.